Iraqi Civil Justice between the Specific Text (The 2009 Compensation for Victims Law) and the General Rules of Tort Liability in Compensating Victims of the Yazidi Genocide - Thamer, Sura (Journal of Legal Sciences, 2026)
Compensating victims of mass violations, particularly the genocide of the Yazidi community, represents one of the fundamental pillars of achieving transitional justice and restoring dignity to victims. The Iraqi legislator has sought to address this issue through Law No. (20) of 2009 on Compensation for Victims of Military Operations, Military Errors, and Terrorist Operations and its amendments, which provided a special legislative framework for compensation. However, this framework faced many practical and substantive challenges in terms of the limited scope of compensation and the difficulties of administrative procedures.On the other hand, Iraqi Civil Code No. 40 of 1951 establishes general rules for compensation in the context of tort liability (Articles 202–231), based on three main pillars: fault, damage, and causation. These rules provide a broader and more comprehensive basis for redressing damages, as they are not limited to material damages alone, but also include moral, psychological, and social damages, and grant civil courts the authority to assess compensation in proportion to the severity of the damage.The research aims to demonstrate the complementary role that civil justice can play by activating the general rules of tort liability to fill the gaps in the specific provisions of the 2009 Law, thus achieving a balance between the requirements of the specific provision and the requirements of civil justice. The study concludes that combining the special law and the general rules of civil liability would ensure more comprehensive compensation and safeguard the rights of victims of the Yazidi genocide, and would enhance community confidence in the Iraqi judicial and legislative system.